Unintended Consequences: Examining the Negative Impact of China's Three-Child Policy and Maternity Leave Extensions on Rural Women's Political Participation - Shushu, Tan; Lucy, Sebli-Seidelson (Oxbridge Publishing House Ltd, 2023)
In the context of rural women's political participation in China, this extensive study examines the complex interactions between demographic changes, traditional cultural values, and gender roles. It does so primarily in light of the Three-Child Policy and extended maternity leave laws. The results of our study shed light on the overall detrimental effects of these policies on the level of involvement of rural women in political activities. The implementation of the Three-Child Policy, in conjunction with the extension of maternity leave, aims to tackle demographic challenges and improve maternal health. However, it unintentionally reinforces long-standing traditional gender norms. The challenges related to an ageing population are highlighted by a notable decrease in the birth rate and a growing proportion of elderly individuals. This also reinforces the widely held belief that women are primarily responsible for domestic duties. The implementation of these policies presents a range of complex obstacles for rural women, which restrict their ability to reintegrate into the workforce and hinder their potential for career advancement. Consequently, this impedes their engagement in political matters. Moreover, this study underscores the importance of adopting a comprehensive policy reform strategy that takes into account the complex interplay between demographics, extended maternity leave, and long-lasting cultural values. The proposed approach places a high emphasis on empowering rural women, with a specific focus on promoting inclusivity and encouraging their active participation in political processes. In summary, this research presents a compelling argument for policymakers to reevaluate existing policies and formulate effective strategies aimed at promoting a society that is characterised by fairness and inclusivity. In addition, it promotes additional investigation through interdisciplinary research, aiming to delve more deeply into the nuanced experiences of rural women and assess the efficacy of potential policy reforms. Collaborative initiatives between academic institutions and women's organisations play a crucial role in advancing gender equality and empowering rural women to actively participate in shaping their communities and the nation.